Dobro wspólne jako naczelna zasada Konstytucji RP z dnia 2 kwietnia 1997 r. - Strzelczyk, Krzysztof (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
What is the common good? What understanding of the common good corresponds to the acknowledgement of the common good principle, stipulated in Article 1 of the Constitution of Poland, to be the fundamental principle? The author of the paper tries to answer these questions and to show that both political and legal interpretations allows us to treat the principle of common good as a normative principle which is not a solely ideological declaration that is not supported by any legal meaning. This paper shows how Article 1 of the Constitution of Poland of 1997 was drafted.